2023
DOI: 10.1101/2023.08.20.554044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Canonical Wnt transcriptional complexes are essential for induction of nephrogenesis but not maintenance or proliferation of nephron progenitors

Helena Bugacov,
Balint Der,
Sunghyun Kim
et al.

Abstract: Wnt regulated transcriptional programs are associated with both the maintenance of mammalian nephron progenitor cells (NPC) and their induction, initiating the process of nephrogenesis. How opposing transcriptional roles are regulated remain unclear. Using anin vitromodel replicatingin vivoevents, we examined the requirement for canonical Wnt transcriptional complexes in NPC regulation. In canonical transcription, Lef/Tcf DNA binding proteins associate the transcriptional co-activator β-catenin. Wnt signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…These data indicate that the basal YAP state in nephron progenitor organoids permits Wnt-induced differentiation, while YAP activation converts the same Wnt signal into a renewal signal when the two temporally overlap. This interaction may relate to the paradoxical requirement of Wnt/β-catenin for both nephron progenitor renewal and differentiation 88 , namely that a rhythmic YAP signaling context could enable the niche to alternately favor each state given a consistent Wnt/β-catenin input in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…These data indicate that the basal YAP state in nephron progenitor organoids permits Wnt-induced differentiation, while YAP activation converts the same Wnt signal into a renewal signal when the two temporally overlap. This interaction may relate to the paradoxical requirement of Wnt/β-catenin for both nephron progenitor renewal and differentiation 88 , namely that a rhythmic YAP signaling context could enable the niche to alternately favor each state given a consistent Wnt/β-catenin input in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…2d). KR5_Mat provides a strong Wnt signal in the early stages of maturation culture, and it has been reported that excessive Wnt signal not only accelerates nephron development but also biases differentiation towards the distal tubules [35][36][37]. Furthermore, Chen et al demonstrated through experiments involving the injection of embryonic mouse NPCs into cap mesenchyme of mouse fetal kidneys at different developmental stages, the developmental timing difference significantly influences the survival and differentiation of injected NPCs [38].…”
Section: Discussionmentioning
confidence: 99%